ANALISIS KETERLAMBATAN PENYELESAIAN LAPORAN KEUANGAN PADA INDUSTRI PERCETAKAN KARTON BOX PT INDORIS PRINTINGDO - Hidayatul Mu’arifin (Universitas Pamulang, 2018)
AbstractThis study aims to determine the factors of delay in the completion of the report on the PT Indoris Printingdo cardboard box printing industry as a whole. This study uses qualitative research methods with interpretive paradigms in order to reveal reality as a construction of experience and awareness in the process of financial statement completion. The population in this research is PT Indoris Printingdo employees have 50 people and are supported by interviews face to face and in writing. Based on the data analysis design used, the following results are obtained: There is a positive and positive influence, 'Significantly between the incomplete transaction evidence, all transactions that are fully recorded in reports, sales and purchase transactions that still have a difference, and a warehouse report that has not been fully recorded against the completion of the financial statements based on the results of the respondents' questionnaire stating that 0.25 or 25% of respondents stated that they did not agree on the statement of all reports on time, which means that all reports were not timely when closing the book so that it had a positive and significant to the timely completion of financial statements. Keywords: delays in financial statements, completion of financial statements